Concert by the Rosé String Quartet, February 15, 1912 (Bonn; Germany; J.F. Carthaus, 2020)
Program for a concert by the Rosé String Quartet at the Beethovenhalle in Bonn on February 15, 1912. The program included Beethoven's String Quartet in C Major, op. 59, no. 3. Includes the text of a letter with an autobiographical sketch written by Haydn on July 6, 1776.